Organocatalytic aminocarbonylation of α, β-unsaturated ketones with N, N-dimethyl carbamoylsilane. (9th April 2021) - Yang, Shou-Shan; Ren, Ying-Zheng; Guo, Yu-Yu; Du, Guang-Fen; Cai, Zhi-Hua; He, Lin
Abstract : Schwesinger's superbase can efficiently activate the Si–CONMe2 bond and initiate the aminocarbonylation of α, β-unsaturated ketones and N, N -dimethyl carbamoylsilane. Abstract : An organic superbase-catalyzed aminocarbonylation reaction of α, β-unsaturated ketones was reported. Under the catalysis of 10 mol% Schwesinger's superbase t -Bu-P4, a variety of enones and ynones reacted with N, N -dimethyl carbamoylsilane to afford α-siloxyamides or α-hydroxyamides in 56–82% yields.